EVALUASI KEBIJAKAN PENDIRIAN BADAN USAHA MILIK DESA - Tatang Sudrajat (POLITEKNIK LP3I JAKARTA, 2021)
The state has provided a lot of welfare to the citizens of rural communities, who make up the largest part of this nation. Socio-economic welfare as a public interest has been pursued by the state with its authority, including in the form of a policy to establish Village Owned Enterprises (BUM Desa). The issuance of Law Number 6 of 2014, PP Number 43 of 2014 and the Village Regulation of PDTT Number 4 of 2015 relating to the interests of the village community, became a strong foundation for the establishment of BUM Desa. In Karawang Regency, this was followed up with the issuance of Regional Regulation Number 4 of 2019 and Perbup Number 35 of 2020. One of the problems when public policy was implemented started from the substance of policies that were bad policy, unclear, not operational/incomplete, ambiguous, and contradictory. The research uses normative juridical methods and literature review. The results of the study indicate that the issue of welfare of rural communities is embodied in various state/government regulations. There is a relationship between the local government as an operational policy maker and the policy environment as well as a hierarchical relationship with policy makers regarding BUM Desa at the national level. There are several policy substances that are considered bad policies, because they are unclear, not operational/incomplete, ambiguous and contradictory. This will have implications for the ineffective implementation of BUM Desa policies by implementers at the lowest level of government.Keywords : evaluation, public policy, village-owned enterprises